Evaluation of Proximate Composition, Antioxidant and Pasting Properties of Optimized Flour Blends from Pearl Millet, Green Gram and Tigernut Pomace - Bello, Florence A.; Oladeji, Babatunde S.; Tom, Rose I. (Food Science and Engineering, 2022)
Flour blends produced from pearl millet, green gram, and tigernut pomace were evaluated for their chemical composition and pasting characteristics. Sixteen runs (flour blends) were generated using optimal mixture design of response surface methodology and used for the determination of functional properties. Four blends were thereafter chosen for the evaluation of the proximate composition, antioxidant, and pasting characteristics. The functional properties of the flour blends had significant (p<0.05) Analysis of Variance (ANOVA), R2, and Adjusted R2 values. An increase in green gram and tigernut pomace flour addition resulted in higher values of ash, crude protein, crude fat, crude fiber, carbohydrate and energy values. The antioxidant properties of the flour blends especially in run 13 (85% pearl millet flour, 5% green gram flour and 10% tigernut pomace flour) showed increases in total phenol, flavonoid and DPPH contents. The pasting profile viscosities were generally low. Pearl millet, green gram and tigernut pomace flour blends could effectively be utilized in the production of complementary food as well as baked products that required low viscosity.